Applicability of Nursing theories by students and their importance for care at different levels of Health Care (Research, Society and Development, 2026)
Introduction: Nursing theories are fundamental for the understanding of phenomena and their aspects within the context of professional practice and can describe, explain, diagnose and even prescribe actions for care practice. Thus, the objective of the present study was to evaluate the knowledge, visualization, perception and applicability of nursing theories by students and to investigate the importance of the theory for professional practice. Methodology: This is an evaluative, exploratory, descriptive and cross-sectional study with a quantitative and qualitative approach. After authorization from the research site, the project was inserted in the Brazil Platform and directed to the Research Ethics Committee (CEP) of the University Center of UNIGRAN de Dourados, with opinion No. 7,280,445. Results and discussion: A total of 71 nursing students participated in the research. Considering this total, the applicability of nursing theories in practice during student care is highlighted, in which only 47.88% of the respondents were aware of the theory to be applied and could easily apply it. Final considerations: This study allowed us to know the challenges faced by the students and the importance of nursing theories in the care and quality of patient care was evidenced, both in Primary Care, with regard to health promotion and prevention, and at the Secondary and Tertiary levels, by demonstrating how health determinant factors directly influence illness, the worsening, improvement and rehabilitation of health.